On the Issue of Criminal Prosecution for Market Abuse in Russia and the EU - MIKHALENKO (KALININA), Yuliya Vladimirovna; SHADRINA, Ekaterina Gennadievna; RASHIDOVA, Asel Ibragimovna (Journal of Advanced Research in Law and Economics; Vol 9 No 4 (2018): JARLE Volume IX Issue 4(34) Summer 2018, 2018)
The securities market is the most attractive area for its bad-faith participants. The transactions are often accompanied by illegal use of insider information and market manipulation, that jeopardizes the economic security of the state and destructively affect the stability of the market. In this regard, the application of liability for the illegal use of insider information and market manipulation becomes an urgent issue. Using scientific research methods, the authors analyze the approaches of European and Russian lawmakers to the issue of criminal prosecution for market abuse and come to the conclusion that there is a need for an integrated approach to improving criminal liability for these offenses; propose changes in the current Russian legislation.